A search for standardized protocols to detect alien invasive crayfish based on environmental DNA (eDNA): A lab and field evaluation. (January 2018) - Geerts, Aurora N.; Boets, Pieter; Van den Heede, Stef; Goethals, Peter; Van der heyden, Christine
Highlights: Environmental DNA is a promising method for detection of lentic macro-invertebrates. Three sampling and three eDNA extraction methods for an invasive crayfish species were tested. Positive identification and DNA yield was highly dependent on sampling, extraction, and primer choice. We propose using filtered (200 ml) samples extracted with the Muyzer protocol. We consider eDNA to be a promising tool for invasive species detection, if reliable and standardized protocols are available. Abstract: Environmental DNA (eDNA) techniques are becoming increasingly popular in conservation and invasion biology, especially for monitoring and early detection of rare, endangered or invasive species. An exponential increase in varying methods regarding eDNA collection and analysis has been observed, which leads to mixed success in detection efficiency in studies on aquatic invertebrates. In this study, we tested and compared three sampling and three DNA extraction methods using the crayfish Procambarus clarkii as model species. Based on existing and newly developed primers, we were able to identify this species from tissue DNA and filtered eDNA samples from water of aquaria kept in the laboratory as well as water from natural ponds. The species could be positively identified in field and laboratory samples, though effectiveness differed greatly. Results in our study seemed to be highly dependent on primer choice, DNA extraction method, and the type of sample (tissue or filter). Our results showed that both an adapted phenol:chlorophorm:isoamyl alcohol protocol and a MasterPure extraction kit provided the most reliable results to detect the species based on tissue and filtered eDNA samples. The results are promising, but also highlight the necessity for a standardized protocol for each step of the eDNA-based monitoring process. These protocols will need to be optimized individually for target groups or species.